Religion, environmental guilt, and pro-environmental support: The opposing pathways of stewardship belief and belief in a controlling god - EOM, Kimin (Institutional Knowledge at Singapore Management University, 2021)
Religion exerts significant influence on how individuals respond to social issues. The present research investigates the implications of religious beliefs on emotions and behaviors regarding environmental issues. In three studies conducted with Christians in the U.S. (N = 1970), we test the model in which stewardship belief and belief in a controlling god are oppositely (i.e., positively for stewardship belief and negatively for belief in a controlling god) associated with environmental guilt, which in turn leads to greater pro-environmental support. We do so by employing both correlational (Studies 1 and 2) and experimental data (Study 3) with diverse measures of pro-environmental support, such as behavioral commitment for environmental organizations (Study 1), policy support (Studies 2 and 3), and financial donation (Study 3). Religion is a system including various beliefs that may have different implications on environmental action. Given the vast number of the religious across the world, understanding this complexity is important to address current global environmental challenges.